Effect of Observer's Sex and Chin Prominences on the Perception of the Lower Lip-Chin Prominence Angle. Issue 2 (14th March 2022) - Lee, Jae-Yeol; Han, Sang Hee; Choi, Youn-Kyung; Kim, Jinmi; Park, Soo-Byung; Kim, Yong-Il
Abstract : Abstract: This study aimed to identify the preferred range of lower lip-chin prominence angles in the Korean population and evaluate the effect of the individual lower lip-chin prominence angle on perceptions of esthetic chin profile. Chin prominence silhouettes were used to assess the lower lip-chin prominence preference. The observers randomly categorized each image as (1) normal, (2) slightly abnormal but not requiring surgical correction, and (3) abnormal and requiring surgery. Individual lower-chin prominence angles of all observers were analyzed using standardized clinical photographs. The normal range of lower lip-chin prominence angle is 0° to 25°; socially acceptable range is 0° to −10°, 25° to 40°; range needing surgery is −10° to −30° and 40° to 45°. Women are more tolerant to chin protrusion. A protrusive chin is more acceptable in observers with retrusive chin profile. Skeletal Class II profile is more acceptable than skeletal Class III in the Korean population. The individual lower-chin prominence angle could affect perception of desired surgery. These findings indicate that patient-specific treatment planning is important in achieving satisfaction in chin surgery.